Medium run redux: technical change, factor shares and frictions in the euro area - Peter McAdam; Alpo Willman (European Central Bank (ECB), 2008)
We develop a framework for analyzing “medium-run” departures from balanced growth, and apply it to the economies of continental Europe. A time-varying factor-augmenting production function (mimicking “directed” technical change) with a below-unitary substitution elasticity coupled with supporting short-run factor demands (and price setting) is shown to account for the observed dynamics of factor incomes shares, capital deepening and the capital-output ratio. Based on careful data accounting, we also identify a rising mark-up, which we ascribe to the rise of Services. The balanced growth path emerges as a special (and testable) case of our framework, as do existing strands of medium-run debates.
Keywords: C22; E23; E25; O30; O51; 330; adjustment costs; Effective Labor Hours; Elasticity of Substitution; euro area; Factor-Augmenting Technical Progress; Income Distribution; Medium Run; productivity; Gleichgewichtiges Wachstum; Dauer; Substitutionselastizität; Technischer Fortschritt; Produktivität; Einkommensverteilung; Dienstleistungssektor; Eurozone; EU-Staaten